Effect of Water on Mechanical Properties of Coal Measures Mudstone Using Nanoindentation - Wenshuai Li; Bangyou Jiang; Shitan Gu (Geofluids)
Mudstone rich in clay minerals exhibits an obvious water-induced weakening effect, and the mechanical properties of mudstone are significantly affected by the groundwater. To investigate the effect of water on mechanical characteristics of mudstone at microscale, a series of uniaxial compression and nanoindentation tests were conducted on mudstone specimens at different moisture contents. Microscale measurements are upscaled to estimate the corresponding magnitudes at the macroscale using the Mori-Tanaka method. The results showed that the indentation modulus varied significantly, from as low as 0.2 GPa to a quite high value of 125 GPa, indicating a strongly heterogeneous distribution of mudstone. The water illustrated a significant effect on the microscale mechanical properties of water-sensitivity minerals like clay minerals. The water-sensitivity minerals occupied the highest proportion of the mudstone and were believed to play an important role in the mechanical properties of mudstone. For water-bearing specimens, the comparison with elastic modulus data obtained from common method indicated similar values as those predicted by homogenization method. The results of this study indicated that nanoindentation technique is a feasible experimental technique to assess the macroscale mechanical properties of rock materials.